Case report: Occupational poisoning incident from a leak of chloroacetyl chloride in Jinan, Shandong, China - Guo, Lanlan; Zhang, Xiangxing; Zhou, Zhiqiang; Shi, Mengdi; Jian, Xiangdong; Dong, Laidong (Frontiers in Public Health, 2023)
Chloroacetyl chloride is a potent acylation agent that decomposes violently in water to produce chloroacetic acid and irritant hydrogen chloride. It and its decomposition products are corrosive to the eyes, skin, and respiratory system and can cause multiple organ failure. Herein, we report cases of poisoning by chloroacetyl chloride and its decomposition products in the skin and respiratory system. After exposure, one patient developed vomiting, irritability, coma, hypoxemia, hypotension, acidosis, and hypokalemia. Another patient developed bronchiolitis, pneumonia, and decreased vision. One patient died and two recovered. Chloroacetyl chloride and its decomposition products are corrosive and can damage multiple organs after absorption through the skin and respiratory tract, leading to severe heart failure. Cardiogenic shock may be the primary cause of early mortality.